A network analysis of angiogenesis/osteogenesis-related growth factors in bone tissue engineering based on in-vitro and in-vivo data: A systems biology approach. (October 2021) - Beheshtizadeh, Nima; Asgari, Yazdan; Nasiri, Noushin; Farzin, Ali; Ghorbani, Mohammad; Lotfibakhshaiesh, Nasrin; Azami, Mahmoud
Graphical abstract: Highlights: Choosing the appropriate protein as a growth factor for tissue engineering applications is vital. Three major biological processes are investigated by creating a PPI network of bone regeneration efficient proteins. Three significant proteins are involved simultaneously in osteogenesis, angiogenesis, and its positive regulatory. To promote angiogenesis and osteogenesis, PTGS2 and FGF18 could be used as growth factors in bone tissue engineering. The function of TEK protein as a growth factor in bone tissue engineering should be determined in future studies. Abstract: The principal purpose of tissue engineering is to stimulate the injured or unhealthy tissues to revive their primary function through the simultaneous use of chemical agents, cells, and biocompatible materials. Still, choosing the appropriate protein as a growth factor (GF) for tissue engineering is vital to fabricate artificial tissues and accelerate the regeneration procedure. In this study, the angiogenesis and osteogenesis-related proteins' interactions are studied using their related network. Three major biological processes, including osteogenesis, angiogenesis, and angiogenesis regulation, were investigated by creating a protein-protein interaction (PPI) network (45 nodes and 237 edges) of bone regeneration efficient proteins. Furthermore, a gene ontology and a centrality analysis were performed to identify essential proteins within a network. The higher degree in this network leads to higher interactions between proteins and causes a considerable effect. The most highly connected proteins in the PPI network are the most remarkable for their employment. The results of this study showed that three significant proteins including prostaglandin endoperoxide synthase 2 (PTGS2), TEK receptor tyrosine kinase (TEK), and fibroblast growth factor 18 (FGF18) were involved simultaneously in osteogenesis, angiogenesis, and their positive regulatory. Regarding the available literature, the results of this study confirmed that PTGS2 and FGF18 could be used as a GF in bone tissue engineering (BTE) applications to promote angiogenesis and osteogenesis. Nevertheless, TEK was not used in BTE applications until now and should be considered in future works to be examined in-vitro and in-vivo .